2005
DOI: 10.1007/s11141-005-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Whistler Wave Emission from a Modulated Electron Beam in a Collisional Magnetoplasma in the Presence of a Density Duct

Abstract: UDC 533.951We study the radiation from a modulated electron beam injected along the axis of a cylindrical density duct in a magnetoplasma. An expression for the average power lost by the beam at the modulation frequency is obtained and analyzed. It is shown that in the case ofČerenkov resonance of the beam with a weakly damped whistler mode of an enhanced-density duct, a noticeable increase in this power is possible compared with the case where the beam is injected in a homogeneous background magnetoplasma. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Moreover, an axially magnetized plasma column surrounded by a dielectric or by free space is able to guide waves propagating in this frequency range. As already shown for the case of modulated beam emission into artificially created density ducts [17,18], the authors expect that a noticeable increase of whistler radiation power should be observed at Cherenkov resonance conditions when the beam is injected into a plasma column surrounded by a dielectric medium, compared to the case when it is injected into a homogeneous unbounded background magnetoplasma. In this paper we aim to demonstrate this fact and to determine the beam radiation power as a function of the medium dielectric permittivity, the main characteristics of the plasma column (radius, plasma density and electron collision frequency) and of the beam (radius and energy).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Moreover, an axially magnetized plasma column surrounded by a dielectric or by free space is able to guide waves propagating in this frequency range. As already shown for the case of modulated beam emission into artificially created density ducts [17,18], the authors expect that a noticeable increase of whistler radiation power should be observed at Cherenkov resonance conditions when the beam is injected into a plasma column surrounded by a dielectric medium, compared to the case when it is injected into a homogeneous unbounded background magnetoplasma. In this paper we aim to demonstrate this fact and to determine the beam radiation power as a function of the medium dielectric permittivity, the main characteristics of the plasma column (radius, plasma density and electron collision frequency) and of the beam (radius and energy).…”
Section: Introductionmentioning
confidence: 72%
“…During the past four decades, a large number of papers have been published regarding the linear and nonlinear theory of whistler wave excitation by pulsed and density modulated electron beams injected in unbounded homogeneous magnetized plasmas (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and references therein). Recently [17][18][19][20], the authors studied the efficiency of whistler radiation by such beams injected along the background magnetic field into density ducts artificially created in laboratory or space plasmas [21][22][23][24][25][26][27][28]. In particular, they showed that the time-averaged power lost by the beam in the presence of a duct of enhanced plasma density can increase noticeably owing to resonant Cherenkov excitation of guided whistler modes at the beam modulation frequency [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21] The authors have already developed a general theory about the resonant linear excitation of waves by modulated electron beams injected parallel to the ambient magnetic field into artificially created cylindrical density ducts in laboratory and space plasmas. [31][32][33] In particular, they have shown that the power radiated by such beams in the presence of enhanced-density ducts increases noticeably due to the Cherenkov excitation of guided whistler modes. In the present work, the theoretical model developed previously 31,32 is extended to the case of spiraling beams radiating in magnetized plasma columns surrounded by homogeneous media as dielectric, free space, or plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] In particular, they have shown that the power radiated by such beams in the presence of enhanced-density ducts increases noticeably due to the Cherenkov excitation of guided whistler modes. In the present work, the theoretical model developed previously 31,32 is extended to the case of spiraling beams radiating in magnetized plasma columns surrounded by homogeneous media as dielectric, free space, or plasma. Such situations can be realized for example in typical laboratory experiments involving whistler excitation by beams or antennas, where the discharge plasma column is often separated from the walls of the setup chamber by a layer of rarefied plasma.…”
Section: Introductionmentioning
confidence: 99%